Labels of Origin for Food Local Development, Global Recognition - Barham, Elizabeth (CABI, 2014)
The majority of the authors of this book belong to a European scholarly network closely connected with the Société française d’économie rurale (the French Society for Rural Economy) and were brought together by a seminar on quality issues in agro-food systems in 1999 (Lagrange, 1999). They have worked individually on many projects at the national level within their home countries, and as a group they have worked together on projects at the scale of the European Union (EU). Bertil Sylvander, co-editor of this volume, led the ﬁ rst EU project, ‘PDO-PGI: Markets, Supply Chains and Institutions’, from 1996 to 1999. The project explored products covered by the EU designations of Protected Designation of Origin (PDO) (also known as Protected Denomination of Origin under particular country programmes of protection) and Protected Geographical Indication (PGI). 1 Results of this joint research ﬁ rst appeared in publications following seminars of the European Association of Agricultural Economists in 1997 (Arﬁ ni and Mora, 1998) and in 1999 (Sylvander et al., 2000).